Marriage Related Suicide Fatality Rates - Fatemeh Akbarizadeh; abdollah hajivandi; Mohammad Hajivandi; Mohammad Sina Zeidabadinejad (Iranian Journal of Psychiatry, 2018)
Objective: The present study aimed at estimating the case fatality rates of suicide acts in different marital status subgroups and to find interrelation with a population living in Bushehr province along the coastal region of the Persian Gulf coast in southwest of Iran.